Pemberdayaan Masyarakat dalam Pengembangan Desa Wisata Sidomulyo, Kediri di Era Kenormalan Baru: Community Empowerment in the Development of Sidomulyo Tourism Village, Kediri in the New Normal Era - Suryandari Istiqomah; Affifah Khoirunnisa; Mochamad Ari Widodo; Kumala Aurani Aziza; Amin Widyaningrum; Prita Noviana; Moh Mashudi; Yania Ifaty Taukhida; Renisya Meilani Kholifi; Fatiha Putri Alma; Nisa’ Nurul Azizah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
This service through the Community Service Program aims to develop tourist villages as an alternative to economic improvement for the Sidomulyo village community in the Pandemic Era through community empowerment. This was done because Sidomulyo Village has one of the tourist objects of the Ganggong Sidomulyo spring (SGS), which local tourists began to visit during the pandemic. Based on the analysis of the problems that have been carried out on the implementation of KKN activities at the Sumber Ganggong Sidomulyo spring tourist spot, Wates District, Kediri Regency, it is focused on providing education about the management of tourist attractions and the importance of implementing health procedures for safe travel. In addition, KKN members also participated in several SGS tourism development activities. This service activity is carried out through active participation and empowerment based on shared ideas, mutual support, flexibility, and cohesiveness which are applied through outreach and practice activities. In practice, both volunteers and village officials are always enthusiastic and fully support each activity. The impact of this KKN activity is that it can increase the knowledge of SGS volunteers in managing and developing SGS tourist attractions and increase awareness of the implementation of health protocol in traveling in the new normal era so that it will be helpful in future practice.